Percepção sobre os determinantes de saúde em caminhoneiros do estado de Sergipe : um estudo qualiquantitativo - Batista, Adriana Maria Figuerêdo (2017)
Faced with the strenuous work routine of the truck driver, added to the life habits adverse to health, this study aims to know the determinants of health among truck drivers in the state of Sergipe, as well as their perception about the theme. This is a cross-sectional study with a qualitative and quantitative approach. The health determinants related to socioeconomic characteristics, health and work conditions, and food choices were evaluated. For a qualitative approach, we used the free evocation technique, individual interviews and focus groups, analyzed through EVOC® software, content analysis and discourse of the collective subject, respectively. There were 146 truck drivers with low schooling (7.0 ± 2.9 years of schooling), overweight (86.8%), hypertriglyceridemia (57.7%), sedentary lifestyle (74.7%), (median of 700 km), followed by long periods without rest (median of 12 hours), and frequent use of amphetamines to inhibit sleep (72.6%). On the other hand, the results indicate a good perception about the importance of adequate food choices. Qualitative information showed a satisfactory self-perception about health (notes 7.5 ± 1.4), denoted by 'absence of disease'. Although it does not have a defined core, the social representation on health pointed to preventive attitudes such as self-care and the reference to the risk imposed by working conditions. The results suggest a morbidity and mortality profile for chronic diseases and a relative understanding of healthy habits, however, with difficulties to put into practice, alleging limitations due to working conditions.